2004
DOI: 10.1359/jbmr.040914
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Terminal Parathyroid Hormone Fragment Analogs Containing α,α-di-alkyl Amino Acids at Positions 1 and 3

Abstract: Constraining the N-terminal PTH backbone conformation with di-alkyl amino acids at positions 1 and 3 may be a general strategy for optimizing and minimizing the PTH pharmacophore; however, inhibitory side-chain effects may be encountered. The new analogs presented should be useful as minimum-length functional probes of the PTH-PTH receptor interaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…In contrast, the agonist profile of MPTH(1-28) is similar to that of PTH(1-34), suggesting that N-terminal AA substitutions increasing a-helicity of the N-terminal domain (Okazaki et al, 2008) help maintain agonist activity of PTH(1-28) analogs. However, introduction of the same AA substitutions into more extensive C-terminal truncated peptides helps predominately to maintain agonist activity to stimulate G s -signaling, as reported by others (Shimizu et al, 2001(Shimizu et al, , 2004Caporale et al, 2009Caporale et al, , 2010Neerup et al, 2011). The structural basis for the greater capacity of PTH(1-28), [Gly 1 ,Arg 19 ]PTH(1-28), ZP2307, and MPTH(1-14) to stimulate receptor internalization is unclear but may be a result of C-terminal AAs present in PTH(1-31) providing a restraint on receptor internalization.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, the agonist profile of MPTH(1-28) is similar to that of PTH(1-34), suggesting that N-terminal AA substitutions increasing a-helicity of the N-terminal domain (Okazaki et al, 2008) help maintain agonist activity of PTH(1-28) analogs. However, introduction of the same AA substitutions into more extensive C-terminal truncated peptides helps predominately to maintain agonist activity to stimulate G s -signaling, as reported by others (Shimizu et al, 2001(Shimizu et al, , 2004Caporale et al, 2009Caporale et al, , 2010Neerup et al, 2011). The structural basis for the greater capacity of PTH(1-28), [Gly 1 ,Arg 19 ]PTH(1-28), ZP2307, and MPTH(1-14) to stimulate receptor internalization is unclear but may be a result of C-terminal AAs present in PTH(1-31) providing a restraint on receptor internalization.…”
Section: Discussionmentioning
confidence: 70%
“…The N-terminal modifications, which typically include conformationally constraining amino acid analogs, such as a-amino isobutyric acid substituted at positions 1 and/or 3, also conferred detectable cAMP-signaling potency to the otherwise inactive PTH(1-11) peptide (Shimizu et al, 2001a(Shimizu et al, ,b, 2004, along with at least some a-helicity (Barazza et al, 2005;Fiori et al, 2007;Caporale et al, 2009aCaporale et al, ,b, 2010Cupp et al, 2013b). It thus may be that for the native ligand, the N-terminal domain becomes structurally more organized as an a-helix upon binding to the receptor (Shimizu et al, 2001b(Shimizu et al, , 2004, as has been suggested for other peptide ligands that bind to a family B GPCR (Parthier et al, 2009).…”
Section: B Parathyroid Hormone-related Proteinmentioning
confidence: 99%
“…To explore the possibility that the slow step of binding related to receptor activation we used [Aib 1,3 , M]PTH(1-14) (see Materials and Methods), a conformationally constrained PTH(1-14)-derived agonist with increased ␣-helicity and similar binding and signaling properties as PTH(1-34) (8,18). Extensive studies have demonstrated that [Aib 1,3 , M]PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and other PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) analogs (8,(19)(20)(21) mainly, if not exclusively, bind to the PTHR J-domain in contrast to PTH(1-34), which binds to both receptor's N-and J-domains (22).…”
Section: Two-mentioning
confidence: 99%
“…Extensive studies have demonstrated that [Aib 1,3 , M]PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and other PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) analogs (8,(19)(20)(21) mainly, if not exclusively, bind to the PTHR J-domain in contrast to PTH(1-34), which binds to both receptor's N-and J-domains (22). When [Aib 1,3 , M]PTH (1-14) is bound, it prevents PTH analogs from occupying their binding site at the J-domain of the receptor (8,18). In the next experiment, we examined whether the specific association of [Aib 1,3 , M]PTH (1)(2)(3)(4)(5)(6)(7)…”
Section: Two-mentioning
confidence: 99%